Traumatic brain injury in Brazil: an epidemiological study and systematic review of the literature - MAGALHÃES, Ana Luísa Gonçalves; BARROS, João Luís Vieira Monteiro de; CARDOSO, Maíra Glória de Freitas; ROCHA, Natália Pessoa; FALEIRO, Rodrigo Moreira; SOUZA, Leonardo Cruz de; MIRANDA, Aline Silva de; TEIXEIRA, Antônio Lúcio (Arquivos de Neuro-Psiquiatria, 2022)
Background: Traumatic brain injury (TBI) is a serious public health problem worldwide. Although TBI is common in developing countries, there are few epidemiological studies. Objective: To investigate the sociodemographic and clinical features of patients with TBI at the Hospital João XXIII, a public reference center for trauma in Belo Horizonte, Brazil, and to systematically review the available literature on TBI in Brazil. Methods: Clinical and sociodemographic data were collected from electronic medical records for the entire month of July 2016. The literature on epidemiology of TBI in Brazil was systematically reviewed using MeSH/DeCS descriptors in the PubMed and Lilacs databases. Results: Most patients admitted with TBI were male and under 60 years of age. Mild TBI was the most prevalent form and the most common cause of TBI was falls. A Glasgow Coma Scale score below 12, neuroimaging changes on computer tomography, and presence of any medical conditions were significantly associated with longer hospital stay. Brazilian studies showed that TBI affected mainly men and young adults. In addition, mild TBI was the most common TBI severity reported and the most common causes were motor vehicle accidents and falls. Conclusions: Overall, the profile of TBI in this center reflects the data from other Brazilian studies.
Keywords: Brain Injuries, Traumatic; Brain Concussion; Epidemiology; Brazil